The unwanted past and urban regeneration of Communist heritage cities. Case study: European Capitals of Culture (ECoC) Riga 2014, Pilsen 2015 and Wroclaw 2016 - Turșie, Corina (Journal of Education Culture and Society, 2020)
Within the ECoC programme, it has been argued that the European dimension is most visible when the candidates reflect their own history as a part of  European history, particularly when hinting at their involvement with the major ideologies of twentieth century, such as National Socialism or Communism. ECoC is about cities re-inventing their identities, re-narrating their history in a European context. But how should ex-communist cities deal with their unwanted past and narrate it in order to fit into the European dimension of the project? The focus of this investigation is on three ex-ECOCs from ex-Communist Europe, chosen for several reasons: geographical position (Central, Eastern/Northern European countries, ex-communist past, new membership of the European Union (since 2004), the year of holding the title (the two ECoC selection criteria exist since 2010). Using qualitative content analysis on a set of documents (application books, official web pages and ex-post evaluations) the study will offer an analysis of cities’ politics of memory and urban regeneration strategies.